(untitled) (Journal of Economic Research & Business Administration, 2015)
In article the investment policy who solves many problems which Kazakhstan in the conditions of industriallyinnovative development of economy, such as maintenance of economic growth, realisation of structural reorganisation, the decision of a problem of employment of the population, maintenance of competitiveness of production in the world market faces is considered.